Prevalence of Tracheoesophageal Anomaly Cases among Neonates Undergoing Surgery in a Tertiary Care Children’s Hospital - Basnet, Bal Mukunda (JNMA J Nepal Med Assoc, 2020)
INTRODUCTION: Tracheo-oesophageal anomaly is the abnormal communication between trachea and oesophagus. The most common type of tracheo-oesophageal anomaly is oesophageal atreasia with distal tracheo oesophageal fistula. Tracheo-oesophageal anomaly is a common neonatal problem requiring an urgent surgery. Tracheo-oesophageal anomaly can be diagnosed as an isolated malformation or as part of polymalformative syndrome with possible vertebrae anomalies also known as Vacterl syndrome. The aim of the study is to find out the prevalence of tracheo-oesophageal anomaly cases among neonates undergoing surgery in a tertiary care childrens hospital in Nepal. METHODS: This is a descriptive cross sectional study conducted in a tertiary care children's hospital in Nepal taking into account the medical records from period of 01 Jan, 2018 to Dec 31, 2019. Study population included the infants undergoing operative procedure in the operation theatre of Kanti Children's Hospital. The calculated sample size was 306. Data was collected by retrospective chart review technique and listed in performa. Consecutive sampling technique was used. Thus collected data was entered in SPSS version 20 and necessary calculations were done. RESULTS: The prevalence of tracheo-oesophageal anomalies was found out to be 30 (9.8%) at 95% confidence interval. The most common problem, with which infants were brought to Kanti Children's Hospital, that required urgent neonatal surgical intervention was anorectal malformation constituting 94 (30.72%) of the surgeries followed by intestinal obstruction 76 (24.84%) which included duodenal atresia, jujunal atresia and ileal atresia. CONCLUSIONS: Tracheo-oesophageal anomaly constitutes a major portion of neonatal disease condition requiring surgery in Nepal.